Interpretation of post-mortem interval by analyzing the histological attributes of gingival mucosa — an observational study - Ananya; Lipsa Bhuyan; Vidya G. Doddawad; Aishwariya Mohanty; Kanika Singh Dhull; Asutosh Das (Egyptian Journal of Forensic Sciences)
Abstract Background Forensic odontology has been one of the most rapidly advancing fields within forensic science for decades. It goes beyond simply determining age and gender, playing a crucial role in estimating the post-mortem interval (PMI), which remains a vital element of forensic investigations. By analyzing post-mortem tissue changes histologically, it offers deep understanding of the time elapsed since death. Although traditional methods for estimating PMI are available, there are limited approaches that specifically utilize histological analysis of gingiva. This study explores the utility of histopathological changes in unfixed antemortem gingival tissues as a means to estimate PMI, leveraging the durability and protection offered by oral mucosa. The research examines autolytic alterations in gingival tissues preserved with formalin over different time intervals, up to 15 days, and analyzes the corresponding histological features to assess their relevance in PMI determination. Results Gingival samples were collected from individuals in a tropical climate and subjected to varying PMIs up to 15 days. Histopathological processing and evaluation were performed to categorize changes into immediate, early, and late stages based on cellular, nuclear, and tissue alterations in the epithelium and connective tissue. Results reveal a progressive degeneration over time, including cytoplasmic vacuolation, pyknotic nuclei, and acantholysis in the epithelium along with connective tissue changes. Endothelial lining disintegration, fibroblast degeneration, and nuclear breakdown were also observed. Epithelium-connective tissue junction integrity is lost, and complete homogenization of tissue occurs beyond 15 days. Conclusion The findings suggest that histopathological analysis of gingival tissue can serve as an additional and potentially reliable method for estimating PMI. It also offer insights into the progression of post-mortem alterations, presenting a feasible, cost-effective, and potentially valuable adjunct method for PMI estimation in certain forensic contexts.